A foliar endophyte increases the diversity of phosphorus-solubilizing rhizospheric fungi and mycorrhizal colonization in the wild grass Bromus auleticus. (October 2015) - Arrieta, A.M.; Iannone, L.J.; Scervino, J.M.; Vignale, M.V.; Novas, M.V.
Abstract: Asexual Epichloë endophytes establish mutualistic symbioses with grasses, improve fitness of their hosts and modify the surrounding environment. To test the hypothesis that this symbiotic association increases the abundance and diversity of phosphate-solubilizing fungi (PSF), a pot experiment was conducted combining two endophytic statuses: Epichloë -infected (E+) and non-infected (E−) Bromus auleticus plants, and two soil types collected from agricultural (A) and non-agricultural (NA) fields. Soil fungi were isolated at the beginning of the experiment and 12 months after the introduction of B. auleticus, and tested for their inorganic P (Pi)-solubilizing capability. Arbuscular mycorrhizal colonization in B. auleticus roots of E+ and E− plants was also analyzed. PSF abundance was affected by the endophytic status and by the type of soil; the highest value was detected in the E−NA treatment, followed by the E+A treatment. PSF diversity was higher in NA than in A soils and higher in soils treated with E+ than in those treated with E−. Arbuscular mycorrhizal fungi colonization was higher in E+ plants. We hypothesize that the positive association between Epichloë endophytes and mycorrhizal fungi with an increase in the PSF diversity would generate an increase in the phosphorus (P) available to plants.